INVESTIGATION OF THE EFFECT OF “HUMAN RELATIONS AND COMMUNICATION COURSE” ON UNIVERSITY STUDENTS' COMMUNICATION AND PROBLEM SOLVING SKILL LEVELS - Akan, Yunus (T.C. Milli Egitim Bakanligi, 2021)
The purpose of this research is to examine the effect of “Human Relations and Communication” on the levels of communication and problem solving skills of university students. This research was designed as a semi-experimental pattern defined as “Pretest-Posttest Control Group Model”. The study group of the research consists of 48 students studying in the Guidance and Psychological Counseling Program of the Faculty of Education in Muş Alparslan University in the 2019-2020 academic years. “Communication Skills Inventory” and “Interpersonal Problem Solving Inventory” were used as data collection tools. The program was applied to the experimental group for 13 weeks on Mondays at 13 o'clock in the training class once a week and 80-90 minutes. Independent sample t-test and ANCOVA (Covariance Analysis) were used to analyze the data of this research. As a result of the research, it was revealed that the “Human Relations and Communication” increased the communication and problem solving skill levels of the students in the experimental group. In line with the results obtained, a literature-supported discussion was held and human relations and communication course content was reviewed and improved, and studies on practice were more involved, the course was spread over two parts in theoretical and practical terms, and that the students of the university and the communication course were taught in all departments. © 2021 Elsevier B.V., All rights reserved.
İNSAN İLİŞKİLERİ VE İLETİŞİM DERSİNİN ÜNİVERSİTE ÖĞRENCİLERİNİN İLETİŞİM VE PROBLEM ÇÖZME BECERİ DÜZEYLERİNE ETKİSİ
Keywords: Beceri Eğitimi; Communication; Human Relations; Problem Solving; Problem Çözme; Skill Education; University Students; Üniversite Öğrencileri; İletişim; İnsan İlişkileri